Uso das praças públicas de Santa Maria durante a pandemia de Covid-19: análise do período de disseminação da variante Ômicron - Melo, Felipe Mulazzani (2023)
This research investigated the effect of the perception of risk of contagion by Covid19, during the dissemination period of the Ômicron variant, on the use of public spaces. The use of three plazas, Saldanha Marinho, João Pedro Menna Barreto and General Osório squares, all in the central region of Santa Maria - RS, were investigated. Observation in loco without user interaction and analysis of security cameras images were used as the main methods of investigation. The number of confirmed cases of Covid-19 reported in the week prior to the observation was adopted as an indicator of the risk of contagion, and an attempt was made to identify changes in visitation behavior, social distancing and mask use. The relationship between risk perception and observed behavior was investigated using an analysis of variance, with differences between contagion in the week of observation and the week before observation as predictor of mask use, social distancing and atendance behavior. As a complementary method to the observed information, an online questionnaire was applied, divided into four sections that presented questions about the following items: ways of using squares, characterization of users, uses, frequency and those indicated in relation to space. Results from the questionnair present an overview of how the interviewees chose to use the squares and their perceptions of plaza sectors during the researched period. Results obtained from observations showed that notifications of increased contagion had an effect on user behavior, reducing attendance and demonstrating effects in mask use and compliance with social distancing. The information collected can help researchers, urban planners and public managers to understand how the population used the square environment and which factors significantly interfere with their routines during the pandemic, thus being able to prepare them more safely for future uses that may arise. situations similar to those experienced during the Covid-19 pandemic.